Synthesis and activities of branched-chain aminoacyl-tRNA synthetases in threonine deaminase mutants of Escherichia coli. - Williams, A L (1978)
Valyl-, isoleucyl-, and leucyl-tRNA synthetase activities were examined in an Escherichia coli K-12 strain that possessed a deletion of three genes of the ilv gene cluster, ilvD, A, and C, and in a strain with the same deletion that also carried the lambdadilvCB bacteriophage. It was observed that the branched-chain tRNA synthetase activities of both strains were considerably less than those of the normal strain during growth in unrestricted medium. Furthermore, during an isoleucine limitation, there was a further reduction in isoleucyl-tRNA synthetase activity and an absence of the isoleucine-mediated derepression of valyl-tRNA synthetase formation in both of these mutants, as compared with the normal strain. In addition, it was observed that these branched-chain synthetase activities were reduced in steady-state cultures of several ilvA point mutants. However, upon the introduction of the ilv operon to these ilvA mutants by use of lambda bacteriophage, there was a specific increase in the branched-chain synthetase activities to levels comparable to those of the normal strain. These results support our previous findings that the stability and repression control of synthesis of these synthetases require some product(s) missing in the ilvDAC deletion strain and strongly suggest this component is some form of the ilvA gene product, threonine deaminase.